Microstructural properties and compressive strength of fly ash-based geopolymer cement immersed in CO2-saturated brine at elevated temperatures - Ridha, S. (Springer Science and Business Media Deutschland GmbH, 2021)
Geopolymer cement has significance in several engineering applications due to improved physical and chemical characteristics compared to ordinary portland cement (OPC). However, the emphasis on petroleum industry for cementing is not well recorded under CO2 exposure. This experimental research aims to investigate the impact of CO2-saturated brine on geopolymer-based and OPC-based cement under elevated temperature. Fly ash-based alkali-activated cement is prepared, and cement slurry is cured at two different conditions (17.23Â MPa/60Â Â°C and 24.13Â MPa/130Â Â°C). The slurry is then submerged into CO2-saturated brine using autoclave chamber at supercritical CO2 conditions for 24, 72 and 96Â h. Microstructure properties are characterized using SEM, XRF, XRD, and IR. Compression strength is experimentally tested on cubical cement samples. A comparative analysis of fly ash geopolymer cement and OPC at varying conditions exhibits that microstructure and compressive strength of geopolymer cement show better performance. It signifies the potential of fly ash as a binder in sequestration cement for CO2 injection wells. This research suggests that the concentration of CO2 has a minor influence on the degree of carbonation. However, the temperature is found to be a critical factor for microstructure and mechanical properties reduction in OPC in a CO2-rich environment. Â© 2021, Islamic Azad University (IAU).